MORFOSINTAKSIS VERBA BAHASA SKOU (Verb Morphosyntac of Skou Language) - Sanjoko, Yohanis (Salingka, 2016)
Skow language is one of local language in Papua Province which relatively has less speaker. This language is spoken by people who live in village of Skou Mabo, Skou Yambe, and Skou Sae. Skou language is used in border territory of Indonesia and Papua New Guinea. This writing discused about Skou language that based on morphosyntac reviewed. The aim of this reseach is to describe verb morphosyntac of Skou language. This writing uses descriptive method with three stages, namely, collecting data stage, analyzing data stage, and presenting the result of analysis data stage. The data, in this writing, was collected by using interview method (metode cakap) through stimulation technique (teknik pancing) as a basic technique while face-to-face interview (cakap semuka) and noting technique (teknik catat) as advanced techniques. The basic data of this reseach are the data of interview result which used instrument, while the supported data are taken from works of Donohue. Then, data analyzing used translational subtype of  equivalent method (metode padan). The result shows that verb morphosyntax Skou language is a kind of language whith extremely rigid verbal agreement. Verbal agreement in Skou language consists of 1) personae, 2) number, and 3) gender. Pattern of active-transitive sentence in Skow language is SOV, while its intransitive  sentences of Skou language pattern is S(S)V with OSV and (S)OSV variants. Skou language is an ergative language.